PENGEMBANGAN OBJEK WISATA RELIGIUS DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DAN PENDAPATAN ASLI DAERAH (PAD) (Suatu studi pada Objek Wisata Bukit Kasih Toar Lumimu’ut kanonang Kabupaten Minahasa). - Rawis, Prisylia; Posumah, Johhny; Pombengi, Jericho Denga (Sam Ratulangi University, 2015)
ABSTRACT : Tourism is one of the things that are important to a country. With the then existing community tourism attractions in the region would memdapatkan positive impact, the public get a chance to open a small business attractions in the region so that a family needs can be met. The local government of tourism objects get revenue from the tourist attraction. The potential of the attraction Hill Love Lumimu'ut district Kanonang minahasa not managed optimally so that the existence of a tourism asset rating not get a positive response in the form of tourist visits. Tourism development is very influential in tourist attraction Hill Love, the following are the factors that inhibit the development of attraction Hill Love Toar Lumimu'ut Kanonang Minahasa .Factors that hamperthe development ofattraction Hill LoveToarLumimu'ut: The quality of human resources is not adequate, System management is not optimal tourism. Manage less society preserve and attractions in Hill Love. Shortage of funds in the development of attraction Hill Love. Tourism marketing and promotion system is not optimal . Inadequate facilities and infrastructure. North Sulawesi provincial government is expected to develop a Tourism attraction Hill Love Toar Lumimu'ut Kanonang Minahasa in increasing people's incomes and the contribution of attraction Hill Love for Local Revenue. This study is qualitative with the observation and interview .for bluntinig techniques of is done directly to people who knowing attraction Hill Love development Kanonang. Key word : Development inÂ Raising Revenue Community And local Revenue